FUNCTIONS OF MULTIMODALITY IN ENEM LANGUAGE TESTS: A COMPARATIVE ANALYSIS - Santiago, Verônica Ferreira; de Lourdes Guimarães de Carvalho, Maria; Nepomuceno, Arlete Ribeiro (Seven Editora, 2025)
Results of a study that aimed to describe the functions of multimodality in language questions from two ENEM exams, one old, from 1998 and one recent, from 2023, and to answer what were the functions of multimodality in the production of meanings in both exams. The hypothesis was that there are differences in functions, from one exam to the other, determined by factors such as precarious resources for inserting multimodal language and the lack of approach to this topic in Portuguese language classes in the 1998s. Specifically, it aimed to (i) explore theoretical assumptions related to the Theory of Multimodality, on literacy, multimodal literacy and considerations on the trajectory of ENEM as a public policy and, (ii) describe the functions of multimodality in Portuguese Language questions from the 1998 exam and the 2023 Languages, Codes and their Technologies exam, analyzing characteristics of the production of meanings. Justified by the importance of highlighting the functions of multimodality in language questions on the ENEM exams, at present, and explaining how much reading proposals have been changing based on new teaching-learning theories and the advent of technology, which has caused social and semiotic changes. DOI: https://doi.org/10.56238/sevened2025.030-042